An investigation of the work-related values of educational managers of private church secondary schools in Malawi, and the implications of the values for OD interventions: a case study - Kadyakapita, Mozecie Spector John (Rhodes University, Faculty of Education, Department of Education, 1999)
One of the organizational change technologies developed in response to the inherent weaknesses of the scientific and classical management theories is organization development (0D). The theories grew out of research experiments in change and training in intergroup relations conducted by Kurt Lewin in 1946 in the United States of America. They have been further developed by other researchers and applied to organizations since then, and to educational organizations since the 1960s. This study was carried out in the light of what some of the 0D esearchers and consultants observed, namely, that 0D interventions tend to be less successful in organizations outside the USA, especially in developing countries. They attributed the lack of success of the interventions to the nature of 0D theories, the skills, attitudes and behaviour of OD consultants, the nature of organizations and, especially, culture. Some of the OD consultants said the culture of the people in developing countries is unreceptive to the values which underpin OD theories. I carried out this study to investigate the work-related values of managers in an educational organization in Malawi, and assess the implications of their values for OD interventions. I used a qualitative case study method and the interview technique to gather data for the study. I also used observation and document analysis techniques to supplement the interview technique. The results of the study indicate that most of the work-related values of the managers closely match the values of OD theories. The findings contradict what some of the OD researchers and consultants said about the culture of the people in developing countries. Hence, OD consultants need to investigate the work-related values of the gatekeepers of cli nt organizations and design and implement OD interventions that fit the interests of the gatekeepers.
Keywords: Church schools -- Malawi; School management and organization -- Malawi; Private schools -- Malawi; Values -- Study and teaching